PSIII-34 Maternal disposition as related to calf weaning performance using chute scores. (5th December 2019) - Sims, Michael; Beck, Paul A; Stewart, Cyril B; Cauble, Reagan
Abstract: Cow disposition has been reported to impact calf performance. The purpose of this study was to investigate the relationship between cow disposition at calving to calf weaning performance. Data were collected from four University of Arkansas research locations on both spring and fall calving herds between August 2017 and May 2018.Cow behavior was observed at calving and received a disposition score (CDS) taken on a 5-point scale where a score of 1 was highly aggressive, and a 5 was apathetic. Calf birthweight (BW), birthdate, and sex were also noted. At weaning, calf weight (WW) was recorded and used to calculate a 205-day adjusted weaning weight (AWW). Calf chute behavior (CS) was taken on a 5-point scale; a score of 1 was indicative of a calm exit, and a 5 was aggressive when exiting the chute. Data were analyzed using the GLIMMIX procedure of SAS. Significance was declared at P ≤ 0.05. Cow Disposition Score had an effect on calf BW (P = 0.0037). Cows that received a disposition score of 2 or 3 had greater calf BW than those who had a disposition score of 4 (P = 0.0021) and (P = 0.0017), respectively. Cow Disposition Score had no effect on calf WW or AWW. Chute Score had an effect on WW (P ≤ 0.05). Calves with a CS of 1 had higher WW than those who had a CS of 2 or 3 (P = 0.028) and (P = 0.005), respectively. Chute Score had an effect on AWW (P = 0.003). Calves that received a CS of 1 had higher AWW than those who had a CS of 2 or 3 (P = 0.0023) and (P = 0.0002), respectively. This study indicates that cows with more aggressive dispositions at calving and calves who had calmer dispositions at weaning had higher performance.